Expected returns to stock investments by angel investors in groups - Ramon P. DeGennaro; Gerald P. Dwyer (Federal Reserve Bank of Atlanta, 2010)
Angel investors invest billions of dollars in thousands of entrepreneurial projects annually, far more than the number of firms that obtain venture capital. Previous research has calculated realized internal rates of return on angel investments, but empirical estimates of expected returns have not yet been produced. Although calculations of realized returns are a valuable contribution, expected returns, rather than realized returns, drive investment decisions. We use a new data set and statistical framework to produce the first empirical estimates of expected returns on angel investments. We also allow for the time value of money, which previous research has typically ignored. Our sample of 588 investments spans the 1972 - 2007 period and contains 419 exited investments. We conduct extensive tests to explore potential bias in the data set and conclude that the evidence in favor of bias is tenuous at best. Our results suggest that angel investors in groups can expect to earn returns that are on the order of returns on venture capital investments. Estimated net returns are about 70 percent in excess of the riskless rate per year for an average holding period of 3.67 years. This estimate is reasonable compared to Cochrane's (2005) estimate of 59 percent per year for venture capital investments, which tend to be in lower-variance, later-stage projects. Returns have a large variance and are heavily skewed, with many losses and occasional extraordinarily high returns.
Keywords: G24; G20; 330; angel investor; expected return; private equity